EFEKTIVITAS PMRI UNTUK MENINGKATKAN MINAT BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA MATERI PECAHAN DISEKOLAH DASAR - Imel Ameylinda Harahap; Raizha Zulfina Harahap (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
Mathematics must be taught from the time children are in elementary school to middle school level. However, students are not very interested in mathematics, and most students find it a difficult subject. The results of PISA 2018 which placed Indonesia in 70th position out of 78 countries, as well as TIMSS 2015 which placed Indonesia in the bottom 6th position, strengthen this. This is caused by mathematics learning that is not varied and abstract, which is contrary to the way elementary school students think. The Indonesian Realistic Mathematics Learning Approach (PMRI) helps students use pragmatic, logical, critical and honest thinking patterns to direct their thinking from real situations to mathematical concepts. Apart from that, students can understand everyday problems through PMRI. The aim of this research is to find out how effective PMRI is in improving the mathematics learning outcomes of grade IV violation students at MIN Setia Bhakti Trawas. This quantitative research is a quasi-experiment with a purposive sampling technique. In this study, tests were used to collect data. The results of research using the N-Gain score test show that the PMRI class's N-Gain score is an average of 52.92%, which is in the quite effective category, while the control class's N-Gain score is an average of 27.44%, which is in the not quite effective category. effective.